Improved Antiproliferative Activity and Fluorescence of a Dinuclear Gold(I) Bisimidazolylidene Complex via Anthracene‐Modification. Issue 24 (30th October 2020) - Jakob, Christian H. G.; Dominelli, Bruno; Schlagintweit, Jonas F.; Fischer, Pauline J.; Schuderer, Franziska; Reich, Robert M.; Marques, Fernanda; Correia, João D. G.; Kühn, Fritz E.
Abstract: A straightforward modification route to obtain mono‐ and di‐substituted anthroyl ester bridge functionalized dinuclear Au(I) bis ‐ N ‐heterocyclic carbene complexes is presented. The functionalization can be achieved starting from a hydroxyl‐functionalized ligand precursor followed by transmetallation of the corresponding Ag complex or via esterification of the hydroxyl‐functionalized gold complex. The compounds are characterized by NMR‐spectroscopy, ESI‐MS, elemental analysis and SC‐XRD. The mono‐ester Au complex shows quantum yields around 18%. In contrast, the corresponding syn ‐di‐ester Au complex, exhibits significantly lower quantum yields of around 8%. Due to insufficient water solubility of the di‐ester, only the mono‐ester complex has been tested regarding its antiproliferative activity against HeLa‐ (cervix) and MCF‐7‐ (breast) cancer cell lines and a healthy fibroblast cell line (V79). IC50 values of 7.26 μM in the HeLa cell line and 7.92 μM in the MCF‐7 cell line along with selectivity indices of 8.8 (HeLa) and 8.0 (MCF‐7) are obtained. These selectivity indices are significantly higher than those obtained for the reference drugs cisplatin or auranofin. Abstract : A simple modification route of hydroxyl functionalized bis ‐NHC dinuclear Au(I) complexes with anthracene is presented, which leads to a significant improvement of the antiproliferative activity and quantum yields up to 18%. By controlling the reaction parameters, one hydroxyl group remains, allowing for further potential bioconjugation to obtain a selective theranostic metal complex.